Molecular phylogeny of South‐East Asian arboreal murine rodents. (25th December 2015) - Pagès, Marie; Fabre, Pierre‐Henri; Chaval, Yannick; Mortelliti, Alessio; Nicolas, Violaine; Wells, Konstans; Michaux, Johan R.; Lazzari, Vincent
Abstract : Recent phylogenetic studies and taxonomic reviews have led to nearly complete resolution of the phylogenetic divisions within the old world rats and mice (Muridae, Murinae). The Micromys division and Pithecheir division are two notable exceptions where groupings of species into these divisions based on morphology and arboreal lifestyle have not been supported by phylogenetic evidence. Several enigmatic species from these divisions have been missing from molecular studies, preventing a rigorous revision of phylogenetic relationships. In this study, we sequenced for the first time one mitochondrial and three nuclear genes from South‐East Asian keystone species of these two arboreal divisions: Hapalomys delacouri ( Micromys division), Lenothrix canus and Pithecheir parvus ( Pithecheir division). We also complemented the molecular data already available for the two divisions with new data from Sundaic Chiropodomys, Indian Vandeleuria oleracea and the recently described Sulawesian Margaretamys christinae . Using this new phylogenetic framework and molecular dating methodologies, our study allows some more detailed classification of the former Micromys and Pithecheir divisions, while confirming their polyphyletic status. Specifically, the former Micromys division should now be split into four monotypic divisions: Chiropodomys, Hapalomys, Micromys and Vandeleuria divisions. The former Pithecheir division is likely to be refined and restricted to Pithecheir and probably Pithecheirops, whereas Lenothrix and Margaretamys should now be recognized as representatives of the Dacnomys division. Our findings have profound implications with regard to the systematics of Murinae, as well as to the early evolution of murine morphology and dental characters.